A retrospective analysis thyroid function and ultrasonography in a group of subjects with lepramatous leprosy in Turkey - Ozkan, Zeynep; Kanat, Zekiye; Alatas, Ozkan; Karagoz, Zuhal Karaca (Public Library Science, 2024)
Background There are several studies on thyroid functions and thyroid gland features in patients with leprosy in the literature. The relationship between them have not been clarified yet. These studies are time-expired and don't contain ultrasonography examination. The purpose of the study is to investigate thyroid functions and gland characteristics in leprosy patients by ultrasonography (US) and current laboratory techniques.Patients and Methods This retrospective study was conducted by collecting the data of patients with lepramatous leprosy. Serum thyroid-stimulating hormone, free triiodothyronine, free thyroxine, anti-thyroid peroxidase, antithyroglobulin, and thyroglobulin values and thyroid ultrasonography reports were collected from previous records.Results The mean age is 75.12 +/- 9.89 years of total 17 subjects and 10 patients (58.8%) were male. Thyroid US was performed on 14 of the patients, nodules were detected in a total of 7 (50%) patients. The mean FT3, FT4, TSH, Anti-Tpo, Anti-TG, and TG values of the patients were found to be within normal limits.Conclusion In the present study, no changes were detected in the thyroid functions and structures of the patients with Lepromatous Leprosy. We consider that prospective randomized studies that will include larger sample sizes are needed to determine whether there is a relationship between leprosy and thyroid disease. Leprosy is also known as Hansen's disease, caused by the bacillus Mycobacterium leprae. This ancient disease continues to be a serious healt problem worldwide. Currently it is more common in subtropical regions. Although leprosy cases are decreasing, they are still seen in Turkey. Mycobacterium Leprae lead to an chronic granulamatous infection mainly on skin and peripheral nerves however, it can also affect other tissues such as eyes, mucous membranes, bones and testicles, and may occur different clinical manifestations. It has been shown that it also causes changes in endocrine organ functions. There are some studies on thyroid functions, but the effects of leprosy on thyroid functions and structure are not clear.In this study, we examined the structural features and functional status of the thyroid gland, in a small number of patients because of Leprosy is non endemic common in our country.No changes were detected in the thyroid functions and structures of the patients with Lepromatous Leprosy in a thyroid-endemic region in this study. We consider that it is necessary prospective randomized studies included larger sample sizes on this topic